HUBUNGAN PERSEPSI KEPEMIMPINAN KEPALA DESA DENGAN KEBERHASILAN PEMBANGUNAN DESA SLOGO KECAMATAN TANON KABUPATEN SRAGEN - Santia, Oky Ayu (Transformasi, 2017)
This research aims to know the relationship of perception of Leadership DevelopmentWith the village chief in the village of the subdistrict Slogo Tanon Sragen. The perception of theleadership of the village head is the result of a reaction carried out by a leader, then it can be saidto be the village head is the way perception or reactionaffect the success of the community in thedevelopment of the village. The success of the construction of the village is the everincreasing the welfare of the inhabitants of the village in question. The method of researchconducted in this research is theuse of quantitative approach with this type of korelasional. Thepopulation here is the entire villagers who lived in the village of the subdistrict Slogo Tanon >Sragen district age group 16 years both men and women, namely of 2,605 people x 5% = 130people, data, research that has been done can be concluded that the results of correlation productmoment correlation value obtained of significance value 0.320 0.001 so there are relationshipperceptions of leadership village chief with the success of the development of the village of thesubdistrict Slogo Tanon Sragen , where the better the leadership of the head of thevillage then further improve success in development of the village.Key word: Perseption, leadership, development